Eksplorasi Filosofi Himpunan dan Geometri dalam Tarian Adat Kangaru Desa Wakalambe dan Boneatiro - Dewi Sartika Sri Wulandari RH; Fatma Erlianti Djafar; Elfira Damayanti; Ernawati Jais (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2022)
Culture and Mathematics cannot be separated. One of Buton's cultures, namely the Kangaru Traditional Dance, cannot be separated from Mathematics. In this dance, contains mathematical concepts in it. The problem is that most Butonese people do not know that a local culture such as the Kangaru Traditional Dance contains mathematical concepts. The purpose of this study was to determine the philosophical meaning of set and geometry in the traditional dance of Kangaru, Wakalambe Village and Boneatiro. This research is a qualitative exploratory research. Where this type of research aims to determine the meaning of each element in the Kangaru Traditional Dance. Data collection techniques in this study used techniques to find reliable sources in the network and used interview techniques for informants or sources online (via telephone). Testing the validity of the data in this study using source triangulation with cross-check technique. The results showed that there was a philosophical meaning that presented the elements of the Kangaru Traditional Dance in sets and geometry. The results of this research will be published through scientific seminars and journals with ISSN as well as obtaining IPR with the hope that the community can transform it into a spirit of mathematics in everyday life.